Beam characterization at NSRL for radiobiological experiments: phase 1 - Burigo, Lucas Norberto; Gehrke, Tim; Jäkel, Oliver; Sivertz, M.; Olsen, T.; Rusek, A.; Obcemea, C.; Greilich, Steffen (Journal of Instrumentation, 2020)
An experimental campaign was carried out at the NASA Space Radiation Laboratory to perform an additional, independent dosimetric characterization of the beams of protons, helium and carbon ions for radiobiological experiments. The campaign was undertaken by the request and with the support from the National Cancer Institute, U.S. In this initial phase, the goals were to obtain a first assessment of the dosimetric reproducibility of the beam control system, including analysis of spatial homogeneity and evaluation of ion beam contamination. They should facilitate the design of further experimental campaigns for beam characterization for radiobiological experiments. Measurements included reference dosimetry with comparison of in-house and external ionization chambers and electrometers, lateral-dose profile measurements in air, depth-dose profile in a water tank, evaluation of water equivalent thickness of a HDPE binary range shifter and estimation of impurities of the investigated helium-ion beam. The experiments and results are presented.